Perancangan Sistem Audio Mobil Berbasiskan Sistem Pakar dan Web - Santoso, Djunaidi; Angga, Angga (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Designing car audio that fits user?s needs is a fun activity. However, the design often consumes more time and costly since it should be consulted to the experts several times. For easy access to information in designing a car audio system as well as error prevention, an car audio system based on expert system and web is designed for those who do not have sufficient time and expense to consult directly to experts. This system consists of tutorial modules designed using the HyperText Preprocessor (PHP) and MySQL as database. This car audio system design is evaluated uses black box testing method which focuses on the functional needs of the application. Tests are performed by providing inputs and produce outputs corresponding to the function of each module. The test results prove the correspondence between input and output, which means that the program meet the initial goals of the design.